The impact of large carnivores on the mortality of semi-domesticated reindeer (Rangifer tarandus tarandus L.) calves in Kainuu, southeastern reindeer-herding region of Finland - Nieminen, Mauri (Rangifer, 2010)
During 2006-2008 the survival of reindeer calves was studied in the reindeer-herding cooperative of Halla in Kainuu area where totally 546 calves were equipped with radio mortality collars mainly at the age of 1-3 days. The survival was monitored from the calving in May until winter round-ups in October to January. The rate, timing and causes of mortality of reindeer were assessed. In 2006-08 totally 177 radio-collared calves were found dead (mean mortality 32.4%) until mid-January. The results showed significant annual variation in calf mortality and predation. Independent of year the mortality of radio-collared calves was highest during the first two months after birth, and the total mortality was 30.7% at the end of October and reached 34.6% by mid-January. The sex of calves and pelt colour did not affect significantly survival of calves. Predation comprised 70.0% of total mortality. Predation by wolf, bear, lynx and wolverine comprised on average 38.4%, 20.3%, 9.0% and 2.3%, respectively. Birth weight of calves lost or killed by predators did not differ from surviving calves. However, birth weight of calves killed by brown bears was significantly lighter (mean 5.84 kg), whereas calves killed by Eurasian lynx was significantly heavier (mean 6.67 kg) than birth weight of calves that survived (mean 6.26 kg). Bears killed calves mainly in May to July, wolves in July to October and lynx in August to December. Of 209 radio-collared adult females, 17 were found dead (8.0%). These females had calved in May and they were killed mainly by wolves (52.0%) in August to October.